Note from the editor: Climate change and contested (economic) futures - Anita Engels (economic sociology_the european electronic newsletter, 2021)
This is the second of three issues of the Newsletter that will be dealing with the topic of climate change. The first has spurred lively comments - from surprise about the plethora of topics and perspectives that economic sociology has to offer on climate change, through a perceived need to engage more in public (economic) sociology, to the idea of creating a European network of economic sociologists working on climate change. Reaching out to invite new authors for the next issue was a great pleasure and brought me interesting new insights.
Keywords: 300